Maternal Serum Uric Acid as a Marker of Predicting Low Birth Weight at Term Pregnancy: A Study Based in CMH Lahore - Ghaffar, Sadia; Nawaz, Qudsia; Shaheen, Zubaida; Shakeel, Shazia; Shafiq, Sadia; Tufail, Nazia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the association of hyperuricemia with adverse pregnancy outcomes in terms of low birth weight at term pregnancy registered at CMH Lahore. Study Design: Prospective cohort study. Place and Duration of Study: Department of Obstetrics and Gynecology of CMH, Lahore Pakistan, from Aug 2018 to Feb 2019. Methodology: A total of 60 pregnant women with a singleton pregnancy were included in the study. Patients with serum uric acid levels greater or equal to 360 umol/L were included in Group-A or the at-risk Group, and Patients with serum uric acid levels less than 360 umol/L were included in Group-B or the control Group. All women were followed till the delivery. Data regarding adverse pregnancy outcomes (low birth weight) was noted. Results: Mean Serum uric acid levels of 380.33±12.92 umol/L in the Exposed Group and mean Serum uric acid levels of 265.66±29.44 umol/L in the Control Group were noted. Low birth weight was seen 12 (40%) in Exposed Group as compared to 7(23.3%) in Unexposed Group (p=0.165) (RR=1.71). Conclusion: Low birth weight at term was not associated with hyperuricemic pregnancy more than normouricemic pregnancy in our study, probably due to the small sample size.